Block copolymer
Patent Information
- Application Number
- JP2022140985
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-09-05
- Publication Date
- 2026-10-22
- Estimated Expiration
- 2042-09-05
Smart Images

Figure 0007939814000001
Abstract
Description
TECHNICAL FIELD
[0001] The present invention relates to a block copolymer excellent in biodegradability, hydrolysis resistance, hot-water decomposability, and handleability. BACKGROUND ART
[0002] From the viewpoint of environmental protection, active development related to bioplastics is being carried out. Polylactic acid, which is a bioplastic, uses plant-derived renewable resources such as corn produced by photosynthesis as raw materials, and is expected to be utilized in a wide range of fields. However, polylactic acid is known to be brittle compared with petroleum-based plastics, inferior in viscosity, flexibility, impact resistance, heat resistance and the like, and further prone to hydrolysis. As an attempt to improve the drawbacks of polylactic acid, for example, techniques utilizing stereocomplexes of polylactic acid have been investigated. For example, Patent Document 1 describes a polyester resin which is a block copolymer (I) containing a polylactic acid unit (a) and a polyester unit (b) as main components and is a stereocomplex for the purpose of being excellent in heat resistance and mechanical properties, as well as a resin composition which contains two or more kinds of the above polyester resins that are the block copolymer (I) and is a stereocomplex. PRIOR ART DOCUMENTS PATENT DOCUMENTS
[0003] PATENT DOCUMENT 1 JP 2011-153275 A SUMMARY OF THE INVENTION PROBLEMS TO BE SOLVED BY THE INVENTION
[0004] The resin or resin composition containing polylactic acid described in Patent Document 1 is presumed to have a certain degree of biodegradability. Here, biodegradability refers to the property of being ultimately broken down into water and carbon dioxide by organisms such as microorganisms, and resins containing polylactic acid are known to exhibit biodegradability in compost. However, with increasing environmental awareness, there is a demand for exhibiting biodegradability over a wider range. Furthermore, final products made from resin materials are required to have hydrolysis resistance in order to suppress the progression of deterioration over time. On the other hand, from the standpoint of environmental protection, it is also useful for resin materials to be recyclable. In order to reuse the raw materials used in resin materials, for example, it is desirable that resin materials be easily decomposed by hot water. Furthermore, resin materials are known to be used in inks and paints, and there is a demand for improved handling properties of resin materials to facilitate coating. Therefore, the object of the present invention is to provide a block copolymer that is excellent in biodegradability, hydrolysis resistance, hydrolysis resistance, and handling in activated sludge and compost. [Means for solving the problem]
[0005] As a result of diligent research to solve the above problems, the inventors of the present invention have come up with the following invention and found that it can solve the problems. In other words, the present invention is as follows.
[0006] [1] A block copolymer comprising a block structural unit (A) mainly composed of polylactic acid units (a) and a block structural unit (B) mainly composed of polyester units (b), wherein the polyester unit (b) contains units derived from an aliphatic diol (b1) and an aliphatic dicarboxylic acid (b2), the aliphatic diol (b1) is an aliphatic diol having an alkyl group as a branched chain and having 5 to 9 carbon atoms, the aliphatic dicarboxylic acid (b2) has 2 to 4 carbon atoms, and the number average molecular weight is 36,000 or less. [2] The block copolymer according to [1] above, wherein the amount of block structural unit (A) is 5% by mass or more and 95% by mass or less, relative to 100% by mass of the total of block structural unit (A) and block structural unit (B). [3] The block copolymer according to [1] or [2] above, wherein the aliphatic diol (b1) has hydroxyl groups at both ends of the main chain. [4] The block copolymer according to any one of [1] to [3] above, wherein the aliphatic diol (b1) is 3-methyl-1,5-pentanediol. [5] The block copolymer according to any one of [1] to [4] above, wherein the aliphatic dicarboxylic acid (b2) is succinic acid. [6] The block copolymer according to any one of [1] to [5] above, wherein the block structural unit (A) consists of a structural unit derived from poly-L-lactic acid or a structural unit derived from poly-D-lactic acid. [7] A block copolymer according to any one of [1] to [6] above, wherein the melting point is less than 185°C. [Effects of the Invention]
[0007] According to the present invention, it is possible to provide a block copolymer that exhibits excellent biodegradability, hydrolysis resistance, hydrolysis resistance, and handling properties in activated sludge and compost. [Modes for carrying out the invention]
[0008] The following description will be based on an example of an embodiment of the present invention. However, the embodiments shown below are illustrative examples for embodying the technical concept of the present invention, and the present invention is not limited to the following description. Furthermore, while preferred embodiments are shown in this specification, combinations of two or more individual preferred embodiments are also preferred embodiments. If there are several numerical ranges for an item indicated by a numerical range, a preferred embodiment can be created by selectively combining the lower and upper limits of those ranges. In this specification, when a numerical range such as "XX~YY" is mentioned, it means "XX or greater and YY or less." In this specification, "~ unit" (where "~" indicates a polymer) means "a structural unit derived from ~". For example, "polylactic acid unit" means "a structural unit derived from polylactic acid," and "polyester unit" means "a structural unit derived from polyester."
[0009] Furthermore, in this specification, the "main chain" of a polymer means the longest molecular chain in the polymer molecule unless otherwise specified. Furthermore, in this invention, "hydrolysis resistance" means resistance to hydrolysis in water at 60°C or lower, preferably 50°C or lower. Hydrolysis resistance can be specifically evaluated by the method described in the examples. Furthermore, in this invention, "hydrothermal decompositionability" refers to decompositionability in hot water exceeding 60°C, preferably 70°C or higher. Hydrothermal decompositionability can be specifically evaluated by the method described in the examples. Furthermore, in this invention, "handlingability" refers to the viscosity of the block copolymer that is suitable for easy application when the block copolymer is used as a resin material in, for example, inks or paints. Handlingability can be specifically evaluated by the method described in the examples.
[0010] The block copolymer of this embodiment contains block structural units (A) mainly composed of polylactic acid units (a) and block structural units (B) mainly composed of polyester units (b), and has a number average molecular weight of 36,000 or less. The inventors conducted various studies on formulations to impart broad biodegradability, excellent hydrolysis resistance, hydrolysis resistance, and ease of handling to block copolymers. As a result, the inventors found that the inclusion of block structural units (A) and (B) in the block copolymer is one effective formulation for achieving biodegradability not only in compost but also in activated sludge, as well as excellent hydrolysis resistance and hydrolysis resistance. In addition, they found that having the number-average molecular weight of the block copolymer within a specific numerical range is one effective formulation for achieving excellent handling. Based on the above results, the inventors conducted further studies and arrived at the present invention.
[0011] The polyester unit (b) contains units derived from an aliphatic diol (b1) and an aliphatic dicarboxylic acid (b2), wherein the aliphatic diol (b1) is an aliphatic diol having an alkyl group as a branched chain and having 5 to 9 carbon atoms, and the aliphatic dicarboxylic acid (b2) has 2 to 4 carbon atoms. Due to the above characteristics, the block structure unit (B) is more likely to become an amorphous polymer, so it is presumed that when the block copolymer biodegrades, microorganisms can easily penetrate the polymer structure, resulting in excellent broad-range biodegradability. Furthermore, it is thought that the aliphatic diol (b1) being composed of a specific number of carbon atoms and having alkyl groups as branched chains contributes to improved biodegradability and hydrolysis resistance. On the other hand, if the block structure unit (B) is not an amorphous polymer, it is thought that microorganisms will have difficulty penetrating the polymer structure when the block copolymer biodegrades, and the effects of the present invention cannot be obtained. However, being an amorphous polymer is only one factor that affects biodegradability. This is because various factors such as whether microorganisms recognize the amorphous structure as food, whether enzymes and microorganisms can easily approach it, steric hindrance of the main chain, melting point, and crystallinity all combine to affect biodegradability. Therefore, it is not the case that the effects of the present invention can be obtained simply by being an amorphous polymer. However, it is not clear why the block copolymer can achieve both broad-range biodegradability and excellent hydrolysis resistance, which are contradictory, by having the polyester unit (b). Furthermore, the fact that the aliphatic diol (b1) is composed of a specific number of carbon atoms and has an alkyl group as a branched chain, and that the aliphatic dicarboxylic acid (b2) is composed of a specific number of carbon atoms, is thought to contribute to the decomposition of the block copolymer in hot water above a certain temperature (preferably 70°C or higher). However, the reason why the block copolymer can have hydrolysis resistance to water below a certain temperature (preferably 50°C or lower) while achieving hydrolysis resistance that makes it easily decomposed in hot water above a certain temperature (preferably 70°C or higher) is unclear.
[0012] [Block structure unit (A)] <Polylactic acid unit (a)> The block structure unit (A) is mainly composed of polylactic acid units (a). The term "main component" above refers to the unit that makes up the block structure unit (A) in the highest proportion. The content of polylactic acid units (a) in the block structure unit (A) is preferably 70% by mass or more, more preferably 80% by mass or more, even more preferably 85% by mass or more, and even more preferably 90% by mass or more, and may contain 100% by mass. There is no upper limit on the amount of polylactic acid units (a) contained in the block structure unit (A), for example, it may be 100% by mass or less.
[0013] The polylactic acid constituting the polylactic acid unit (a) may be prepared by direct condensation of lactic acid or by ring-opening polymerization of lactide. As the lactic acid, for example, at least one selected from the group consisting of L-lactic acid, D-lactic acid, and DL-lactic acid can be used. As the lactide, for example, at least one selected from the group consisting of L-lactide, D-lactide, DL-lactide, and meso-lactide can be used. Furthermore, polylactic acid can be poly-L-lactic acid, poly-D-lactic acid, poly-DL-lactic acid, or stereocomplex polylactic acid obtained by mixing poly-L-lactic acid and poly-D-lactic acid. From the viewpoint of cost and raw material availability, at least one polylactic acid selected from the group consisting of poly-L-lactic acid, poly-D-lactic acid, and poly-DL-lactic acid is preferred, and at least one polylactic acid selected from the group consisting of poly-L-lactic acid and poly-D-lactic acid is more preferred. On the other hand, from the viewpoint of synthesis cost, complexity, and processability of block copolymers, it is preferable that the polylactic acid is not a stereocomplex polylactic acid. From the viewpoints of further superior biodegradability and hydrolysis resistance, the block structural unit (A) contains a structural unit derived from poly-L-lactic acid or a structural unit derived from poly-D-lactic acid, preferably in an amount of 70% by mass or more, more preferably 80% by mass or more, and still more preferably 90% by mass or more. For example, an example of a preferred embodiment is that the block structural unit (A) consists of a structural unit derived from poly-L-lactic acid or a structural unit derived from poly-D-lactic acid, that is, the content of the structural unit derived from poly-L-lactic acid or the structural unit derived from poly-D-lactic acid is 100% by mass.
[0014] 〈Unit (a') other than polylactic acid unit (a)〉 The block structural unit (A) may or may not contain a unit (a') other than the polylactic acid unit (a). The monomer constituting the unit (a') is not particularly limited within a range that does not impair the effects of the present invention. In the block structural unit (A), the content ratio of the unit (a') is preferably 30% by mass or less, more preferably 20% by mass or less, still more preferably 15% by mass or less, and even more preferably 10% by mass or less.
[0015] 〈Number average molecular weight of block structural unit (A)〉 The number average molecular weight of the block structural unit (A) is preferably 1,000 to 100,000, more preferably 2,000 to 50,000, still more preferably 3,000 to 25,000, and may be 3,000 to 15,000. Within the above numerical range, further superior hydrolysis resistance and handleability can be exhibited. When the block copolymer has a plurality of block structural units (A), the number average molecular weight of the block structural unit (A) means the sum of the number average molecular weights of all the block structural units. The number average molecular weight of the block structural unit (A) can be determined from the number average molecular weight of the block copolymer described later and the mass content of the block structural unit (A).
[0016] [Block structural unit (B)] The block structure unit (B) is mainly composed of polyester units (b). The term "main component" above refers to the unit that makes up the block structure unit (B) in the highest proportion. The content of polyester units (b) in the block structure unit (B) is preferably 50% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, even more preferably 85% by mass or more, and particularly preferably 90% by mass or more, and may contain 100% by mass. There is no upper limit on the amount of polyester units (b) contained in the block structure unit (B), for example, it may be 100% by mass or less. Polyester unit (b) contains units derived from an aliphatic diol (b1) and an aliphatic dicarboxylic acid (b2). Specifically, polyester unit (b) contains units derived from a polyester obtained by reacting an aliphatic diol (b1) and an aliphatic dicarboxylic acid (b2). Polyester unit (b) may or may not contain units derived from monomers other than aliphatic diols (b1) and aliphatic dicarboxylic acids (b2). Other monomers besides the aliphatic diol (b1) and aliphatic dicarboxylic acid (b2) are not particularly limited as long as they do not impair the effects of the present invention. The total amount of aliphatic diol (b1) and aliphatic dicarboxylic acid (b2) in polyester unit (b) is preferably 90% by mass or more, more preferably 95% by mass or more, even more preferably 99% by mass or more, and may be 100% by mass. Furthermore, there is no upper limit on the total amount of aliphatic diol (b1) and aliphatic dicarboxylic acid (b2) in polyester unit (b), for example, it may be 100% by mass or less.
[0017] <Aliphatic diol (b1)> Aliphatic diols (b1) are aliphatic diols having an alkyl group as a branched chain and having 5 to 9 carbon atoms. Here, the "branched chain" in aliphatic diol (b1) refers to a substructure that branches off from the "main chain" of aliphatic diol (b1), and no hydroxyl groups are bonded to its ends. Furthermore, the "main chain" in the aliphatic diol (b1) refers to a substructure that is a molecular chain composed of multiple atoms, preferably carbon atoms, connecting the two hydroxyl groups in the molecule, with the two hydroxyl groups at both ends. Therefore, the two hydroxyl groups in the aliphatic diol (b1) are located at both ends of the "main chain" in the aliphatic diol (b1).
[0018] Furthermore, the "number of carbon atoms" mentioned above refers to the total number of carbon atoms in the aliphatic diol (b1), including the number of carbon atoms forming the alkyl group. If the aliphatic diol (b1) has 4 or fewer carbon atoms, it may have poor hydrolysis resistance. Furthermore, if the aliphatic diol (b1) has 10 or more carbon atoms, it may have poor biodegradability. From the viewpoint of achieving even better hydrolysis resistance, the number of carbon atoms in the aliphatic diol (b1) is preferably 6 to 9.
[0019] When the aliphatic diol (b1) does not have a branched chain that is an alkyl group, the block structural unit (B) tends to crystallize easily and hydrolysis resistance deteriorates. Therefore, block copolymers cannot exhibit broad biodegradability and excellent hydrolysis resistance. Furthermore, in the aliphatic diol (b1), the number of branched chains is preferably one or two, more preferably one. The branched chains are preferably a methyl group, an ethyl group, and a propyl group, more preferably a methyl group and an ethyl group, and even more preferably a methyl group. If the aliphatic diol (b1) has multiple branched chains, each branched chain may be the same or different.
[0020] Aliphatic diols (b1) include, for example, 2,2-dimethyl-1,3-propanediol, 2-ethyl-1,3-propanediol, 2-ethyl-2-methyl-1,3-propanediol, 2-methyl-1,4-butanediol, 1,2-pentanediol, 1,3-pentanediol, 2,3-pentanediol, 2,4-pentanediol, 2-methyl-2,4-pentanediol, 1,4-pentanediol, and 2-methyl-1,5-pentanediol. Examples include ol, 3-methyl-1,5-pentanediol, 2-methyl-2,4-pentanediol, 2-ethyl-1,5-pentanediol, 2,4-dimethyl-1,5-pentanediol, 2,4-diethyl-1,5-pentanediol, 1,2-hexanediol, 1,3-hexanediol, 1,4-hexanediol, 1,5-hexanediol, 2-ethyl-1,6-hexanediol, and 2-methyl-1,8-octanediol. The aliphatic diol (b1) is preferably 3-methyl-1,5-pentanediol and 2,4-diethyl-1,5-pentanediol, and more preferably 3-methyl-1,5-pentanediol. Aliphatic diol (b1) may be used alone or in combination of two or more types.
[0021] <Aliphatic dicarboxylic acid (b2)> The number of carbon atoms in an aliphatic dicarboxylic acid (b2) is between 2 and 4. Aliphatic dicarboxylic acids (b2) with 5 or more carbon atoms may have poor hydrolysis resistance. Aliphatic dicarboxylic acids (b2) with 4 or fewer carbon atoms are effective in achieving both hydrolysis resistance and hydrolysis resistance. From the viewpoint of ease of production of block copolymers due to the thermal stability of the monomer, the number of carbon atoms in the aliphatic dicarboxylic acid (b2) is preferably 3 or 4, and more preferably 4.
[0022] Examples of aliphatic dicarboxylic acids (b2) include oxalic acid, malonic acid, and succinic acid. From the viewpoint of easily achieving both excellent hydrolysis resistance and hydrothermal decomposition resistance, as well as ease of manufacturing block copolymers, succinic acid is preferred as the aliphatic dicarboxylic acid (b2). Aliphatic dicarboxylic acid (b2) may be used alone or in combination of two or more types.
[0023] <Preferred combinations of aliphatic diol (b1) and aliphatic dicarboxylic acid (b2)> From the viewpoint of exhibiting even better biodegradability, hydrolysis resistance, and hydrothermal decomposition resistance, the combination of 3-methyl-1,5-pentanediol and succinic acid, and the combination of 2,4-diethyl-1,5-pentanediol and succinic acid are examples of preferred embodiments, and the combination of 3-methyl-1,5-pentanediol and succinic acid is an example of a more preferred embodiment.
[0024] <Ratio of aliphatic diol (b1) to aliphatic dicarboxylic acid (b2)> The molar ratio [aliphatic diol (b1) / aliphatic dicarboxylic acid (b2)] used when reacting an aliphatic diol (b1) with an aliphatic dicarboxylic acid (b2) is preferably 1.4 / 1 to 1 / 1.4, and more preferably 1.2 / 1 to 1 / 1.2.
[0025] <Polyester units other than (b) (b')> The block structure unit (B) may or may not contain units other than the polyester unit (b), such as (b'). The monomers constituting unit (b') are not particularly limited as long as they do not impair the effects of the present invention. The content of unit (b') in block structural unit (B) is preferably 50% by mass or less, more preferably 30% by mass or less, even more preferably 20% by mass or less, even more preferably 15% by mass or less, and particularly preferably 10% by mass or less.
[0026] <Number-average molecular weight of block structural units (B)> The number-average molecular weight of the block structural unit (B) is preferably 1,000 to 100,000, more preferably 2,000 to 50,000, and even more preferably 3,000 to 30,000, and may also be 4,000 to 25,000. Within the above numerical range, block copolymers tend to be easier to manufacture. The number-average molecular weight of block structural units (B) can be determined from the number-average molecular weight of the block copolymer (described later) and the mass content of block structural units (B), and can be measured specifically by the method described in the examples.
[0027] [Structural Unit Ratio] With respect to the total mass of block structural units (A) and block structural units (B) of 100% by mass, block structural unit (A) preferably accounts for 5% to 95% by mass. If the proportion of the above block structural unit (A) is 5% by mass or more, the block copolymer tends to have excellent strength and heat resistance. Furthermore, if the proportion of the above block structural unit (A) is 95% by mass or less, it tends to have excellent flexibility, impact resistance, and biodegradability. From the viewpoint of strength and heat resistance, the proportion of the above block structure unit (A) is more preferably 10% by mass or more, and even more preferably 15% by mass or more. Furthermore, from the viewpoint of flexibility, impact resistance and biodegradability, the proportion of the above block structure unit (A) is more preferably 80% by mass or less, and even more preferably 75% by mass or less. The proportion of block structural units (A) is, 1 It can be determined by 1H-NMR, and specifically by the method described in the examples.
[0028] Furthermore, the total content ratio of block structural units (A) and block structural units (B) in the block copolymer is preferably 90% by mass or more, more preferably 95% by mass or more, and may be 100% by mass. There is no upper limit on the total content ratio of block structural units (A) and block structural units (B) in the block copolymer; for example, it may be 100% by mass or less.
[0029] The block copolymer may or may not contain units other than block structural unit (A) and block structural unit (B). Units other than block structure unit (A) and block structure unit (B) are not particularly limited as long as they do not impair the effects of the present invention. In the block copolymer, the content of units other than block structural unit (A) and block structural unit (B) is preferably 10% by mass or less, more preferably 5% by mass or less.
[0030] [Bonding patterns of block copolymers] The bonding form of the block copolymer is preferably triblock or diblock, with the triblock form being more preferred. The block copolymer may also be a mixture of triblock and diblock forms. Specifically, the bonding form is preferably [block structural unit (A)]-[block structural unit (B)]-[block structural unit (A)].
[0031] [Number-average molecular weight of block copolymers] The number-average molecular weight of the block copolymer is 36,000 or less. If the number-average molecular weight of the block copolymer exceeds 36,000, the viscosity of the block copolymer may increase, potentially leading to poor handling. From the viewpoint of ease of manufacture and processability of the block copolymer, the number-average molecular weight of the block copolymer is preferably 35,000 or less, and more preferably 25,000 or less. From the viewpoint of the strength and heat resistance of the block copolymer, the number-average molecular weight of the block copolymer is preferably 5,000 or more, more preferably 8,000 or more, and even more preferably 10,000 or more. In other words, the number-average molecular weight of the block copolymer is preferably 5,000 or more and 35,000 or less. The number-average molecular weight of the block copolymer can be determined by gel permeation chromatography (GPC), specifically by the method described in the examples.
[0032] [Melting point of block copolymer] From the viewpoint of processability, such as facilitating melt processing, the melting point of the block copolymer is preferably less than 185°C, more preferably 180°C or lower, even more preferably 160°C or lower, and may also be 150°C or lower. From the viewpoint of practical heat resistance as a resin material, the melting point of the block copolymer is preferably 110°C or higher, more preferably 120°C or higher, and even more preferably 125°C or higher. From the viewpoint of good processability and heat resistance, the melting point of the block copolymer is preferably 110°C or higher and less than 185°C. The melting point of the block copolymer can be determined by differential scanning calorimeter, and specifically by the method described in the examples.
[0033] <Glass transition temperature of block copolymers> The glass transition temperature of the block copolymer is preferably between -80°C and -15°C. Within this numerical range, the block copolymer tends to exhibit excellent flexibility and impact resistance. From the viewpoint of low-temperature properties such as impact resistance at low temperatures, the glass transition temperature of the block copolymer is more preferably -20°C or lower, even more preferably -25°C or lower, and may also be -30°C or lower. A lower lower limit for the glass transition temperature of the block copolymer is preferable, but for example, it may be -70°C or higher, -60°C or higher, -50°C or higher, or -40°C or higher. The glass transition temperature of a block copolymer can be determined by differential scanning calorimetry.
[0034] [Method for manufacturing block copolymer] A known manufacturing method can be used to produce the block copolymer. Known methods for producing block copolymers may include, for example, synthesizing polyesters that constitute polyester units (b) and polymerizing the polyesters with lactide. The above polyester can be synthesized by known methods. For example, polyester can be synthesized by reacting an aliphatic diol (b1) and an aliphatic dicarboxylic acid (b2) using an esterification catalyst (e.g., tin octylate, tin chloride, tin oxide). When polymerizing polyester and lactide, it is preferable to use a ring-opening polymerization catalyst (e.g., tin octylate, tin chloride, tin oxide). Polymerization reactions can include solution polymerization, melt polymerization, and interfacial polycondensation, and known polymerization reaction conditions can be set for all of these.
[0035] Another known method for producing block copolymers may involve synthesizing polylactic acid constituting polylactic acid units (a) and polyester constituting polyester units (b), and then reacting the polylactic acid with the polyester. Polylactic acid can be synthesized by known methods. For example, polylactic acid may be synthesized by directly reacting lactic acid by a condensation method, or by reacting lactide by a ring-opening polymerization method. When polymerizing polylactic acid and polyester, it is preferable to use an esterification catalyst (for example, tin octylate, tin chloride, or tin oxide). Polymerization reactions can include solution polymerization, melt polymerization, and interfacial polycondensation, and known polymerization reaction conditions can be set for all of these. [Examples]
[0036] The present invention will be described in detail below with reference to examples and comparative examples, but the present invention is not limited to these.
[0037] The compounds used in the examples and comparative examples are as follows: 3-Methyl-1,5-pentanediol (manufactured by Kuraray Co., Ltd.) Adipic acid (manufactured by Tokyo Chemical Industry Co., Ltd.) Tin octoate (manufactured by Tokyo Chemical Industry Co., Ltd.) Toluene (manufactured by Kishida Chemical Co., Ltd.) L-lactide (manufactured by Tokyo Chemical Industry Co., Ltd.) Methanol (manufactured by Fujifilm Wako Pure Chemical Corporation) 2,4-Diethyl-1,5-pentanediol (manufactured by Tokyo Chemical Industry Co., Ltd.) 2-Methyl-1,3-propanediol (manufactured by Tokyo Chemical Industry Co., Ltd.) Succinic acid (manufactured by Tokyo Chemical Industry Co., Ltd.) 1,4-Butanediol (manufactured by Tokyo Chemical Industry Co., Ltd.)
[0038] The physical properties of the block copolymers in the examples and comparative examples were measured or evaluated by the following methods. (1) Number average molecular weight (Mn) The number-average molecular weight (Mn) of the above block copolymer was determined on a standard polystyrene basis by gel permeation chromatography (GPC). The Mn of block structural units (B) was determined from the Mn of the block copolymer and the mass content of block structural units (B). <GPC measurement conditions> Equipment: GPC system "HLC-8220" manufactured by Tosoh Corporation Separation column: Tosoh Corporation "TSKgel SuperMultiporeHZ-M (column diameter = 4.6 mm, column length = 15 cm)" (two columns connected in series) Eluent: Tetrahydrofuran (THF) Eluent flow rate: 0.35mL / min Column temperature: 40℃ Detection method: Differential refractive index (RI) Injection volume: 10μL Concentration: 1 mg / 1 mL (block copolymer / THF)
[0039] (2) Hardness ratio (mass %) (mass content of block structural units (A) mainly composed of polylactic acid units (a)) 1 The hard ratio of the block copolymer was calculated by 1H-NMR. The molar ratio of block structural unit (A) to block structural unit (B) was calculated from the area ratio of the signal around 5.2 ppm originating from the polylactic acid unit and the signal around 0.9 ppm originating from structural unit (B) mainly composed of polyester unit (b) in the obtained spectrum. The mass ratio was obtained by multiplying this molar ratio by the molecular weight of the block structural unit, and the mass ratio of block structural unit (A) when the sum of these mass ratios was adjusted to 100 was defined as the hard ratio. < 1 Measurement conditions for H-NMR Equipment: Nuclear magnetic resonance apparatus “JNM-ECX400” manufactured by JEOL Ltd. Solvent: Deuterated chloroform Measurement temperature: 50℃ Total number of times: 1024
[0040] (3) Biodegradable (compost) The biodegradability of the block copolymer in compost was measured according to the method specified in ISO 14855-2:2018. After 15 days, a degradation rate of 20% by mass or more was rated A, 10% by mass or more but less than 20% by mass was rated B, and 5% by mass or more but less than 10% by mass was rated C.
[0041] (4) Biodegradable (activated sludge) The biodegradability of the block copolymer in activated sludge was measured according to a method conforming to ISO 14851:2019. After 90 days, a degradation rate of 5% by mass or more was evaluated as A, and a degradation rate of less than 5% by mass was evaluated as B.
[0042] (5) Handling The complex viscosity was measured using a rotary viscoelasticity measuring device under the following conditions. Handling ease was evaluated as follows: a complex viscosity value of less than 10,000 Pa·s at 160°C was rated A, and a value of 10,000 Pa·s or more was rated B. <Measurement conditions for complex viscosity> Equipment: TA Instruments Rotary Viscoelasticity Measurement Device "ARES-G2" Angular frequency: 1Hz Heating rate: 2°C / min Furthermore, if the complex viscosity value is less than 10,000 Pa·s, for example, when used as a paint, it tends to have a moderate viscosity that makes it easy to apply and offers excellent handling properties. On the other hand, if the complex viscosity value is 10,000 Pa·s or more, for example, when used as a paint, it tends to have a viscosity that makes it difficult to apply and offers poor handling properties.
[0043] (6) Hydrolysis resistance (h) The above block copolymer was dissolved in chloroform at a concentration of 10% by mass, and then poured onto a glass plate to prepare a 200 μm thick film. A 0.15 g sample was then cut out and used as the test sample. The obtained test sample was immersed in 50 mL of deionized water at pH 7 and left at 50°C. The number-average molecular weight was measured at predetermined intervals, and the elapsed time until the molecular weight fell to less than 90% of the initial number-average molecular weight was evaluated. The longer the elapsed time, the better the hydrolysis resistance. If the elapsed time exceeds 400 hours, it will be indicated as ">400h" in the table.
[0044] (7) Hydrothermal decomposition (h) The above block copolymer was dissolved in chloroform at a concentration of 10% by mass, and then poured onto a glass plate to prepare a 200 μm thick film. A 0.15 g sample was then cut out and used as the test sample. The obtained test sample was immersed in 50 mL of deionized water at pH 7 and left at 70°C. The number-average molecular weight was measured at predetermined intervals, and the elapsed time until the molecular weight fell to less than 90% of the initial number-average molecular weight was used for evaluation. The shorter the elapsed time, the better the hydrothermal decomposition performance. If the elapsed time exceeds 200 hours, it will be indicated as ">200h" in the table.
[0045] (8) Melting point (°C) The melting point of the block copolymer described above was measured using a differential scanning calorimeter according to the method described in JIS K7121:2012. If multiple peaks were observed, the melting point derived from the highest temperature peak was taken as the melting point of the block copolymer. Equipment: Mettler-Toledo DSC822 Differential Scanning Calorimetry Spectrometer Measurement conditions: Heating rate 10°C / min
[0046] [Example 1] In a flask equipped with apparatus for distilling off the generated liquid and a vacuum pump, 3-methyl-1,5-pentanediol and succinic acid were charged in a molar ratio of 3-methyl-1,5-pentanediol / succinic acid = 1.1 / 1. Then, tin octylate was added in an amount of 0.1% by mass relative to the total mass of 3-methyl-1,5-pentanediol and succinic acid. The reaction was carried out under a nitrogen atmosphere, at atmospheric pressure, by heating at 160°C for 3 hours and then at 220°C for 3 hours, while distilling off the water. Next, the reaction was carried out under reduced pressure to 2,000 Pa for 3 hours, and then under reduced pressure to 80 Pa, while checking as needed until the number average molecular weight reached 10,000, thereby synthesizing a polymer consisting of structural units (B') mainly composed of polyester units. After the reaction was complete, the pressure was returned to atmospheric pressure, the temperature was cooled to 80°C, and then toluene was added to dilute the solid content to 40% by mass. The toluene solution was then added to twice the volume of methanol of the total solution. The supernatant was discarded, and the mixture was washed again with methanol in the same amount as the toluene solution that had been added. The supernatant was discarded, and the recovered insoluble matter was dried in a vacuum dryer at 40°C to remove organic volatiles, yielding a polymer consisting of structural units (B') mainly composed of polyester units. Toluene was added again to the polymer consisting of the purified structural unit (B') to dilute it to a solid content concentration of 33% by mass. Then, the temperature was raised to 140°C to remove 10% by mass of the added toluene by distillation, thereby dehydrating the system. The mixture was then cooled to 80°C, and the polymer consisting of structural unit (B') and L-lactide were added in a mass ratio of polymer consisting of structural unit (B') / L-lactide = 50 / 50. Further, the amount of toluene removed by distillation as described above was added to adjust the solid content concentration to 50% by mass. Subsequently, the temperature was raised to 100°C, and 0.1% by mass of tin octylate was added relative to the polymer consisting of structural unit (B'), and the mixture was reacted for 4 hours to obtain a toluene solution of a block copolymer consisting of block structural unit (A) mainly composed of polylactic acid units (a) and block structural unit (B) mainly composed of polyester units (b). Toluene was added to this solution to dilute the solid content to 40% by mass. Then, the toluene solution was added to twice the volume of methanol to precipitate the solid. The supernatant methanol was discarded, and the same amount of methanol as the added toluene solution was added again for washing. The methanol was discarded, and the recovered solid was dried at 40°C in a vacuum dryer to remove organic volatiles, yielding a block copolymer consisting of block structural units (A) mainly composed of polylactic acid units (a) and block structural units (B) mainly composed of polyester units (b). The obtained block copolymer was subjected to the measurements and evaluations described above. The results are shown in Table 1.
[0047] [Examples 2-5] A block copolymer consisting of a block structural unit (A) mainly composed of polylactic acid units (a) and a block structural unit (B) mainly composed of polyester units (b) was synthesized in the same manner as in Example 1, except that the number-average molecular weight was adjusted by adjusting the reaction time during the synthesis of the polymer consisting of structural units (B') mainly composed of polyester units, the mass ratio of the L-lactide used was changed, and the dilution concentration during synthesis was appropriately changed to a concentration that is easy to handle. The obtained block copolymer was subjected to the measurements and evaluations described above. The results are shown in Table 1.
[0048] [Example 6] Except for using 2,4-diethyl-1,5-pentanediol instead of 3-methyl-1,5-pentanediol and adjusting the number-average molecular weight by adjusting the reaction time during the synthesis of the polymer consisting of a structural unit (B') mainly composed of polyester units, a block copolymer consisting of a block structural unit (A) mainly composed of polylactic acid units (a) and a block structural unit (B) mainly composed of polyester units was synthesized in the same manner as in Example 1. The obtained block copolymer was subjected to the measurements and evaluations described above. The results are shown in Table 1.
[0049] [Comparative Example 1] A block copolymer consisting of a block structural unit (A) mainly composed of polylactic acid units (a) and a block structural unit (B) mainly composed of polyester units (b) was synthesized in the same manner as in Example 1, except that the number-average molecular weight was adjusted by adjusting the reaction time during the synthesis of the polymer consisting of structural units (B') mainly composed of polyester units, and the dilution concentration during synthesis was appropriately changed to a concentration that is easy to handle. The obtained block copolymer was subjected to the measurements and evaluations described above. The results are shown in Table 1.
[0050] [Comparative Example 2] Except for using 2-methyl-1,3-propanediol instead of 3-methyl-1,5-pentanediol and adjusting the number-average molecular weight by adjusting the reaction time during the synthesis of the polymer consisting of the polyester unit-based structural unit (B'), a block structural unit (A) mainly composed of polylactic acid units and a block copolymer consisting of the polyester unit-based block structural unit were synthesized in the same manner as in Example 1. The obtained block copolymer was subjected to the measurements and evaluations described above. The results are shown in Table 1.
[0051] [Comparative Example 3] Except for using adipic acid instead of succinic acid and adjusting the number-average molecular weight by adjusting the reaction time during the synthesis of the polymer consisting of polylactic acid units (a) and block copolymers consisting of polylactic acid units (A) and block structural units consisting of polyester units, the procedure was the same as in Example 1. The obtained block copolymer was subjected to the measurements and evaluations described above. The results are shown in Table 1.
[0052] [Comparative Example 4] Except for using 1,4-butanediol instead of 3-methyl-1,5-pentanediol and adjusting the number-average molecular weight by adjusting the reaction time during the synthesis of the polymer consisting of a structural unit (B') mainly composed of polyester units, a block structural unit (A) mainly composed of polylactic acid units and a block copolymer consisting of a block structural unit mainly composed of polyester units were synthesized in the same manner as in Example 1. The obtained block copolymer was subjected to the measurements and evaluations described above. The results are shown in Table 1.
[0053] [Table 1]
[0054] The compounds represented by the abbreviations in Table 1 are as follows: PLLA: Poly-L-lactic acid MPD: 3-methyl-1,5-pentanediol DEPD: 2,4-diethyl-1,5-pentanediol MPDiol: 2-methyl-1,3-propanediol BD:1,4-butanediol AA: Adipic acid SA: Succinic acid
[0055] As shown in the examples in Table 1, the block copolymer of this embodiment, which includes block structural units (A) mainly composed of specific polylactic acid units (a) and block structural units (B) mainly composed of polyester units (b), was confirmed to exhibit excellent biodegradability in both compost and activated sludge applications. Furthermore, the block copolymer of this embodiment, as shown in the examples in Table 1, was confirmed to have a suitable melting point and excellent handling properties. In addition, the block copolymer of this embodiment, as shown in the examples in Table 1, was confirmed to have hydrolysis resistance to water at 50°C while also exhibiting hydrolysis resistance to hot water at 70°C, thus achieving both hydrolysis resistance and hydrolysis resistance. Thus, because the block copolymer of this embodiment is hydrolysis-resistant, it is expected that, for example, the block copolymer used as a resin material can be reused as a raw material for resin materials after undergoing hydrolysis. On the other hand, the block copolymer obtained in Comparative Example 1 had high complex viscosity and poor handling properties. This result is thought to be due to the block copolymer having an excessively high number-average molecular weight. Furthermore, the block copolymer obtained in Comparative Example 2 showed lower hydrolysis resistance compared to the example. This result is thought to be due to the fact that the aliphatic diol used as a raw material has fewer than 5 carbon atoms. Furthermore, the block copolymer obtained in Comparative Example 3 showed inferior hydrothermal decomposition properties compared to the example. This result is thought to be due to the fact that the dicarboxylic acid used as a raw material has more than 4 carbon atoms. Furthermore, the block copolymer obtained in Comparative Example 4 did not exhibit good biodegradability and showed inferior hydrolysis resistance compared to the examples. This result is thought to be due to the fact that the aliphatic diol used as a raw material had fewer than 5 carbon atoms, and furthermore, the aliphatic diol did not have alkyl groups as branched chains.
[0056] As shown in the above examples, the block copolymer of this embodiment exhibits broad biodegradability and excellent resistance to hydrolysis, hydrolysis, and handling. Therefore, the industrial utility of the block copolymer of this embodiment is extremely high.
Claims
1. This is a block copolymer containing block structural units (A) mainly composed of polylactic acid units (a) and block structural units (B) mainly composed of polyester units (b). The polyester unit (b) contains units derived from an aliphatic diol (b1) and an aliphatic dicarboxylic acid (b2), wherein the aliphatic diol (b1) is an aliphatic diol having an alkyl group as a branched chain and having 5 to 9 carbon atoms, and the aliphatic dicarboxylic acid (b2) has 2 to 4 carbon atoms. The aforementioned block structural unit (A) consists of structural units derived from poly-L-lactic acid or structural units derived from poly-D-lactic acid. The number-average molecular weight of the aforementioned block structural unit (B) is between 1,000 and 17,000. The number-average molecular weight is 36,000 or less. Its melting point is less than 185°C. Block copolymer.
2. The block copolymer according to claim 1, wherein the polylactic acid constituting the polylactic acid unit (a) is not a stereocomplex polylactic acid.
3. The block copolymer according to claim 1, wherein the melting point is 160°C or lower.
4. The block copolymer according to any one of claims 1 to 3, wherein the amount of block structural unit (A) is 5% by mass or more and 95% by mass or less, relative to a total of 100% by mass of the block structural unit (A) and the block structural unit (B).
5. The block copolymer according to any one of claims 1 to 3, wherein the aliphatic diol (b1) has hydroxyl groups at both ends of the main chain.
6. The block copolymer according to any one of claims 1 to 3, wherein the aliphatic diol (b1) is 3-methyl-1,5-pentanediol.
7. The block copolymer according to any one of claims 1 to 3, wherein the aliphatic dicarboxylic acid (b2) is succinic acid.
8. The block copolymer according to any one of claims 1 to 3, wherein the block structural unit (A) consists of a structural unit derived from poly-L-lactic acid or a structural unit derived from poly-D-lactic acid.
Citation Information
Patent Citations
Aliphatic polyester copolymer and its production
JP1998204160A
Catalyst for producing polyester and method for producing polyester
JP2002053648A
Aliphatic polyester polyether copolymer composition
JP2007186545A
Polyester resin, resin composition and molded body using the same
JP2011153275A
Lactic acid-base resin compositions and molded articles made thereof
WO2002006400A1